Tree resistance outweighs climatic drivers in governing extreme growth suppression - Yuntao Dong; Ouya Fang; Ying Deng; Jiangshan Lai; Hengfeng Jia (iScience, 2025)
Summary: While climate extremes are conventionally considered primary triggers of extreme growth suppression (EGS) in trees, the role of trees’ intrinsic resistance capacity in mediating EGS remains a persistent knowledge gap. By analyzing 4,599 EGSs across 2,631 juniper trees at 61 sites on the Tibetan Plateau, we quantified the influence of intrinsic and extrinsic factors on EGS using a random forest model and a piecewise structural equation model. The results showed tree resistance exerted 1.7× greater effect on EGS likelihood than climatic variables of the current year, mediated through both direct physiological pathways and indirect age-related effects. Tree age negatively modulated resistance capacity. These findings fundamentally challenge the climate-centric paradigm in dendroecology, which emphasizes the critical role of individual tree physiology in mediating climate responses. Our mechanistic framework advances a predictive model of forest dynamics under climate change by integrating resilience with traditional climate-growth relationships.